Laryngeal Kaposi’s sarcoma - Case report - Silva, Clara (2011)
Kaposi’s sarcoma (KS), is the most common malignancy observed in the patient with acquired immune deficiency syndrome (AIDS). Head and neck involvement is not unusual. However laryngeal involvement with dyspnoea is rare. The authors present a clinical case that illustrates this pathology as the first manifestation of AIDS.A 37 year-old male, with no prior pathology, with history of hoarseness, dysphagia and dyspnoea within 2 months. He presented with a supraglottic neoformation, and a biopsy of the lesion and a tracheotomy were performed. Complementary exams confirmed the diagnosis of laryngeal KS associated to human immunodeficiency virus (HIV) infection. He started chemotherapy, opportunistic infection prophylaxis and antiretroviral therapy. There was total regression of the lesions and he was decanulated after the 4th cyle of chemotherapy. This entity, rare as the initial manifestation of AIDS, must be considered in the differential diagnosis of laryngeal mass.